Probing the structural and electronic properties of doped gallium oxide and sulfide, M(GaX2)2 where M = alkali or coinage metal; X = O, S. Issue 128 (14th December 2015) - Seeburrun, N.; Alswaidan, I. A.; Fun, H.-K.; Archibong, E. F.; Ramasami, P.
Abstract : A theoretical study on the equilibrium geometries, vibrational frequencies and electronic features of a series of doped gallium oxide and sulfide clusters, M(GaX2 )2 (M = alkali or coinage metal; X = O or S), was conducted. Abstract : A theoretical study on the equilibrium geometries, vibrational frequencies and electronic features of a series of doped gallium oxide and sulfide clusters, M(GaX2 )2 (M = alkali or coinage metal; X = O or S), was conducted. The ground and low-lying excited states of these clusters were studied using DFT, MP2 and single point CCSD(T) levels of theory, in conjunction with 6-311+G(2df) and Stuttgart quasi-relativistic pseudo-potential (SDD) basis sets. In most cases, the substitution of an alkali or coinage metal atom in the gallium oxide and sulfide clusters does not drastically affect the structural characteristics. The vertical electron detachment energies (VEDEs) of gallium oxide and sulfide doped with alkali metals range from 2.88 [CCSD(T)//B3LYP] to 4.51 (B3P86) eV while with the coinage metals, the values vary from 3.36 [CCSD(T)//MP2] to 6.92 (MP2) eV. The VEDEs of coinage-gallium sulfide clusters namely Cu(GaS2 )2, Ag(GaS2 )2 and Au(GaS2 )2 are higher than that of GaS2 . This feature is observed as the extra electron of the anion is localized mainly around the GaS2 moiety. Furthermore, anions with high VEDEs interacted with a positive counter ion to form salts. The fragmentation energies indicate that the studied clusters are stable.